Argumentasi Penolakan Rasisme dalam Al-Qur’an - Mabrur (Al-Fanar: Jurnal Ilmu Al-Qur’an dan Tafsir, 2021)
This article examines and analyzes the arguments for the rejection of the Al-Qur'an against acts or views of racism. To understand this, there are three very substantial and logical reasons for rejecting the action. First, the affirmation of the Al-Qur'an about the dignity of human dignity which is legitimized by God based on QS. Al-Isrā’ [17]: 70. Second, the arguments of the Al-Qur'an in QS. al-Ḥujurāt [49]: 13 concerning plurality as a necessity that demands mutual respect and respect for others. Third, the firm ultimatum of Al-Qur'an in QS. al-Ḥujurāt [49]: 11 on the prohibition of insulting and insulting one particular group. To elaborate the arguments of the Qur'an, the researcher tries to analyze, understand and conclude with the maqashidi interpretive approach to explain the spirit, spirit and ideal-moral of the Qur'an as formulated by Abdul Mustaqim. Therefore, the assumption that is built is that the presence of the Al-Qur'an within the scope of human life is to create harm and prevent damage (mafsadat). With this step, leading to a concrete conclusion that the actions, attitudes or views of racism are a form of "arrogance" against plurality, on the other hand it is considered to be injurious to the principles of humanity that have been laid down by God.